Enhancement of Non‐Gaussianity and Nonclassicality of Photon‐Added Displaced Fock State: A Quantitative Approach. Issue 1 (20th November 2022) - Malpani, Priya; Thapliyal, Kishore; Banerji, J.; Pathak, Anirban
Abstract: Non‐Gaussian and nonclassical states and processes are already found to be important resources for performing various tasks related to quantum gravity and quantum information processing. Considering these facts, a quantitative analysis of the nonclassical and non‐Gaussian features is performed here for photon added displaced Fock state, as a test case, using a set of measures, namely entanglement potential, Wigner–Yanese skew information, Wigner logarithmic negativity, and relative entropy of non‐Gaussianity. It is observed that Fock parameter always increases the amount of nonclassicality and non‐Gaussianity, while photon addition is effective only for small values of the displacement parameter. Further, the nonclassical and non‐Gaussian effects decrease initially with an increase in the displacement parameter before increasing for the large displacement to saturate to the corresponding Fock state (equivalently displaced Fock state) value. Finally, dynamics of the Wigner function under the effect of photon loss channel is used to show that only highly efficient detectors are able to detect Wigner negativity. Abstract : A quantitative analysis of non‐Gaussian and nonclassical aspects of photon added displaced Fock state is performed using a number of measures, like Wigner–Yanese skew information, entanglement potential, Wigner logarithmic negativity, and relative entropy of non‐Gaussianity. Robustness of the negativity of the Wigner function over different noise channels is also studied.